THE IMPACT OF INSTITUTIONAL OWNERSHIP, RETURN ON ASSETS, CURRENT RATIO ON TAX AVOIDANCE MODERATED BY FIRM SIZE ON COMPANIES ON THE IDX - Azwar, Khairul; Susanti, Elly; Putri, Juan Anastasia; Sianipar, Ruth Tridianty; Ervina, Nelly (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Taxes are mandatory contributions to the state that are owed by individuals or entities that are coercive based on the law, by not getting direct rewards and used for state purposes, especially for the prosperity of the people. This study aims to determinethe impact of KI, ROA, CR on tax avoidance and to find out whether the size of the company is able to moderate the influence of KI, ROA, CR on tax avoidance. This research period was carried out during 2017 –2023.The sampling technique used in this study is purposive sampling. The data analysis technique that will be used is to use simple regression analysis, and Residual Test to moderate variables. The results of the F test gave results that KI, ROA, CR had a positive and significant effect on tax avoidance. The results of the t-test showed that KI had a positive and insignificant effect on avoidance. Meanwhile, ROA and CR have a positive and significant effect on avoidance. The results of the residual test show that the size of the company is not able to moderate the influence of KI, ROA, CR on tax avoidance.